2020
DOI: 10.1002/ldr.3639
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the 2D–scale, location–specific variations of soil properties in the coal mining area of Changhe watershed, China

Abstract: Many researches have been conducted to understand the scale-location specific variations of soil properties in one-dimensional soil samples. However, these results did not enable us to properly understand the 2D (two-dimensional) distributions of soil characteristics, especially in the coal mining areas. Therefore, the objective of this study is to reveal the scale-location dependent variation of two-dimensional patterns for soil properties and to develop a soil organic matter (SOM) prediction based on those s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
4
0
0
Order By: Relevance
“…The spatial distribution of the residual (Figure 4a5,b5) was closest to that of the original distribution (Figure 3a,b), which illustrated the overall spatial trend in soil salinity. These results are consistent with those of Huang et al (2017), Zhou et al (2021), and Zhu et al (2020). Wei et al (2021) decomposed soil salinity into seven scales using the WT algorithm in the region, while more than five scales were used in this study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The spatial distribution of the residual (Figure 4a5,b5) was closest to that of the original distribution (Figure 3a,b), which illustrated the overall spatial trend in soil salinity. These results are consistent with those of Huang et al (2017), Zhou et al (2021), and Zhu et al (2020). Wei et al (2021) decomposed soil salinity into seven scales using the WT algorithm in the region, while more than five scales were used in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Future studies are required to clarify the effects of soil erosion on salinization. Our study found that removing the influence of the scale component of small‐scale variability (i.e., IMF1‐IMF4) enhanced the correlation between soil salinity and environmental factors (Tables 3 and 4), which is similar to the findings of other studies (Zhang et al, 2021; Zhu et al, 2020). Therefore, the adoption of scale‐specific environmental factors might improve the estimation of soil salinity or other soil properties and reduce the uncertainty in digital soil mapping.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations